Improving Power Flow Capacity of Transmission Lines Using DPFC with a PEM Fuel Cell - Chakravorty, J.; Saraswat, J. (Engineering, Technology & Applied Science Research, 2019)
The electrical power system is one complex architecture integrating generation, transmission, distribution, and utilization sections. The exponential increase in power requirements made this system more complex and dynamic. Providing good quality and uninterrupted power has become a challenge. In this respect, FACTS devices are playing a vital role in improving power quality and also in increasing the transmission capacity of lines. In this paper. Distributed Power Flow Controller (DPFC), with a PEM fuel cell, has been used in an IEEE-14 bus system to improve system power flow capacity. The proposed IEEE-14 bus with DPFC has been simulated in MATLAB/SIMULINK. The effects are exhibited and analyzed.